2009
DOI: 10.1212/wnl.0b013e3181c55d02
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic nuclei activity in idiopathic generalized epilepsy

Abstract: We demonstrated in humans the involvement of the centromedian and parafascicular part of the corticoreticular system and of the anterior nucleus part of the limbic system during generalized spike-and-wave discharges. The different time courses suggest that the posterior intralaminar nuclei may be involved in epileptic discharge initiation or early propagation, while the anterior nucleus may only play a role in its maintenance. These results may help to understand the clinical effect of deep brain stimulation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 14 publications
5
94
0
Order By: Relevance
“…7 However, little attention has been paid to the functional topographic pathways linking distinct cortical areas and specific thalamic nuclei. 10,11 These projections likely have distinct roles in the mechanism of GSWDs, 12 so it is essential to investigate corticothalamic functional networks in generalized epilepsy. More precisely, characterizing epicenters within each network may facilitate the development of targeted surgical interventions (eg, deep brain stimulation) that selectively disrupt seizures and ultimately improve the clinical treatment of IGE.…”
Section: Abbreviationsmentioning
confidence: 99%
“…7 However, little attention has been paid to the functional topographic pathways linking distinct cortical areas and specific thalamic nuclei. 10,11 These projections likely have distinct roles in the mechanism of GSWDs, 12 so it is essential to investigate corticothalamic functional networks in generalized epilepsy. More precisely, characterizing epicenters within each network may facilitate the development of targeted surgical interventions (eg, deep brain stimulation) that selectively disrupt seizures and ultimately improve the clinical treatment of IGE.…”
Section: Abbreviationsmentioning
confidence: 99%
“…28,29 However, a recent EEG-fMRI study found that posterior intralaminar nuclei may be involved in the initiation of epileptic discharges and the anterior nucleus may play a role in seizure maintenance. 6 Variable findings are likely due to varying methods of measurement (e.g., voxel-based morphometry, manual volumetrics), combining left and right findings, chronological age, duration of epilepsy at MRI, and heterogeneity of IGE group. In the current study, as- sessment of volume early in the course was useful in removing the confounding influence of duration of epilepsy.…”
Section: Aed Frequencymentioning
confidence: 99%
“…Since Gloor et al 3 first suggested that an abnormal cortical response to thalamocortical afferents might be responsible for generalized seizures, there is considerable evidence that thalamocortical networks are pathophysiologic in IGE. [4][5][6] Previous imaging studies have shown consistent structural and functional thalamic and cortical abnormalities, particularly in the frontal lobes, 7,8 and thalamofrontal white matter connectivity. 5 The thalamus and frontal lobes have extensive anatomic interconnectivity with bidirectional pathways 9 and both structures are involved in generalized spike wave discharges associated with IGE.…”
mentioning
confidence: 91%
“…In the following 50 years, results supporting either the cortical or thalamic origin of SWDs have been reported (Avoli 2012). In the most recent studies, investigators employed the simultaneous EEG and/or functional magnetic resonance imaging (fMRI) recordings at multiple cortical and thalamic sites and saw the precursor activity in specific cortical areas prior to SWD onset in animal models (Meeren et al 2002;David et al 2008) as well as in human patients (Tyvaert et al 2009;Bai et al 2010). These findings provide the most compelling evidence supporting that the cortex is actually the initiator of SWDs, although technical limitations prevented the simultaneous monitoring of every thalamic and cortical area or subareas potentially involved in SWDs in these studies (Luttjohann and van Luijtelaar 2015).…”
Section: Pathological Function Of Ca V 32 Channelsmentioning
confidence: 99%